Conductive paste for gravure printing, electronic component, and multilayer ceramic capacitor
By optimizing the composition and structure of the conductive paste, especially selecting suitable organic solvents and binder resins, the problem of corrugation caused by low viscosity paste is solved, and the consistency and reliability of the internal electrode layer of the laminated ceramic capacitor is improved. sex.
Patent Information
- Application Number
- CN202180062800.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-02
- Filing Date
- 2021-10-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-10-25
AI Technical Summary
In gravure printing, the low viscosity conductive paste causes an increase in the corrugation of the dry film surface, affecting the consistency of the thickness of the electrode layer inside the laminated ceramic capacitor, and reducing the reliability of the equipment.
Conductive slurry including conductive powder, ceramic powder, dispersant, binder resin and organic solvent are used, and the specific components include isobornacetate, methyl isobutyl ketone and diisobutyl ketone, etc., and the organic solvent content is The content of dispersant is more than 3% and less than 60%, the content of dispersant is more than 0.05% and less than 3.0%, the content of binder resin is more than 0.5% and less than 10%, the content of ceramic powder is more than 1% and less than 20%, the content of binder is more than 1% and less than 20%, the content of binder is more than 1% and more than 20%, the content of binder is more than 1% and more than 20%. The resin is a cellulose-based resin. The average particle size of the conductive powder is between 0.05 μm and 1.0 μm, the average particle size of the ceramic powder is between 0.01 μm and 0.5 μm, and the viscosity at a shear rate of 100 sec-1 is 3 Pa· The viscosity at the shear rate of 10000 sec-1 is 1 Pa·S or less.
The surface corrugation of the dry film is effectively reduced, the filmization quality and productivity of the internal electrode layer are improved, and the reliability of the laminated ceramic capacitor is ensured.
Smart Images

Figure CN116113671B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste for gravure printing, an electronic component, and a multilayer ceramic capacitor. Background Art
[0002] As electronic devices such as mobile phones and digital devices become smaller and more powerful, electronic components including multilayer ceramic capacitors are also expected to be smaller and have higher capacitance. Multilayer ceramic capacitors have a structure in which multiple dielectric layers and multiple internal electrode layers are alternately stacked. By thinning the dielectric layers and internal electrode layers, miniaturization and higher capacitance can be achieved.
[0003] A multilayer ceramic capacitor is manufactured, for example, in the following manner. First, a conductive paste for internal electrodes is printed in a predetermined electrode pattern on the surface of a ceramic green sheet containing a dielectric powder such as barium titanate (BaTiO3) and a binder resin, and the mixture is dried to form a dry film. Next, the dry film and the ceramic green sheet are stacked in an alternating overlapping manner to obtain a laminate. Next, the laminate is heated and pressed to form an integrated body to form a pressed body. The pressed body is cut, and after being treated to remove the organic binder in an oxidizing atmosphere or an inert atmosphere, it is fired to obtain a fired chip. Next, a paste for external electrodes is applied to both ends of the fired chip, and after firing, the surface of the external electrode is plated with nickel, etc. to obtain a multilayer ceramic capacitor.
[0004] As a printing method used when printing a conductive paste on a dielectric green sheet, screen printing has been generally used in the past. However, due to the demands for miniaturization, thin filmization, and improved productivity of electronic devices, there is a demand for printing finer electrode patterns with higher productivity.
[0005] As one of the printing methods of conductive paste, a gravure printing method as a continuous printing method is proposed, in which a conductive paste is filled in a concave portion provided in a plate-making, and the conductive paste is pressed against the printed surface, thereby transferring the conductive paste from the plate-making. The gravure printing method has a fast printing speed and excellent productivity. When using the gravure printing method, it is necessary to appropriately select the binder resin, dispersant, solvent, etc. in the conductive paste, and adjust the properties such as viscosity to a range suitable for gravure printing.
[0006] For example, Patent Document 1 discloses a conductive paste for forming an internal conductor film by gravure printing, wherein the internal conductor film is an internal conductor film in a multilayer ceramic electronic component having a plurality of ceramic layers and an internal conductor film extending along a specific interface between the ceramic layers, wherein the conductive paste comprises 30 to 70% by weight of a solid component containing a metal powder, 1 to 10% by weight of an ethyl cellulose resin component having an ethoxy content of 49.6% or more, 0.05 to 5% by weight of a dispersant, and a solvent component as the remainder, and the conductive paste is a conductive paste having a shear rate of 0.1 (s-1 ) when the viscosity η 0.1 The shear rate is 1Pa·s or more and 0.02(s -1 ) when the viscosity η 0.02 A thixotropic fluid that satisfies the conditions expressed by a specific formula.
[0007] In addition, Patent Document 2 describes a conductive paste which is used to form an internal conductor film by gravure printing, similarly to Patent Document 1, and which contains 30 to 70 wt % of a solid component containing a metal powder, 1 to 10 wt % of a resin component, 0.05 to 5 wt % of a dispersant, and a solvent component as the remainder, and has a shear rate of 0.1 (s -1 ) when the viscosity is 1Pa·s or more, at a shear rate of 0.1(s -1 ) as the reference, the shear rate is 10(s -1 ) is more than 50%.
[0008] According to the above-mentioned Patent Documents 1 and 2, the above-mentioned conductive paste is a paste having a shear rate of 0.1 (s -1 ) can achieve stable continuous printing at high speed in gravure printing, and can manufacture multilayer ceramic electronic components such as multilayer ceramic capacitors with good production efficiency.
[0009] In addition, Patent Document 3 describes a conductive paste for gravure printing, which is a conductive paste for internal electrodes of a multilayer ceramic capacitor comprising a conductive powder (A), an organic resin (B), an organic solvent (C), an additive (D), and a dielectric powder (E), wherein the organic resin (B) is composed of polyvinyl butyral having a degree of polymerization of 10,000 or more and 50,000 or less and ethyl cellulose having a weight average molecular weight of 10,000 or more and 100,000 or less, and the organic solvent (C) is composed of any one of propylene glycol monobutyl ether, a mixed solvent of propylene glycol monobutyl ether and propylene glycol methyl ether acetate, or a mixed solvent of propylene glycol monobutyl ether and mineral spirits, and the additive (D) is composed of a separation inhibitor and a dispersant, and the separation inhibitor is composed of a composition containing a polycarboxylic acid polymer or a polycarboxylate. According to Patent Document 3, the conductive paste has a viscosity suitable for gravure printing, can improve the uniformity and stability of the paste, and has good drying properties.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2003-187638
[0013] Patent Document 2: Japanese Patent Application Publication No. 2003-242835
[0014] Patent Document 3: Japanese Patent Application Publication No. 2012-174797 Summary of the invention
[0015] Problems to be solved by the invention
[0016] Conductive pastes for gravure printing are required to have low viscosity. However, in low-viscosity conductive pastes, the waviness of the film surface tends to become larger when forming a dried film compared to high-viscosity conductive pastes for screen printing and the like. When such conductive pastes are used to form internal electrode layers of multilayer ceramic capacitors, the film thickness of the obtained internal electrode layers varies, which reduces the reliability of the multilayer ceramic capacitors.
[0017] In view of such circumstances, an object of the present invention is to provide a conductive paste for gravure printing having a small waviness on the surface of a dried film.
[0018] Means used to solve problems
[0019] In a first aspect of the present invention, there is provided a conductive paste for gravure printing, comprising conductive powder, ceramic powder, a dispersant, a binder resin, and an organic solvent, wherein the organic solvent contains at least one selected from the group consisting of isobornyl acetate, methyl isobutyl ketone, and diisobutyl ketone.
[0020] In addition, preferably, the conductive paste further comprises a dicarboxylic acid of 0.05 mass % or more and less than 3.0 mass % relative to the conductive paste as a whole. In addition, preferably, the conductive paste comprises an organic solvent of 10 mass % or more and 60 mass % or less relative to the conductive paste as a whole. In addition, preferably, the conductive paste comprises a dispersant of 0.01 mass % or more and 3.0 mass % or less relative to the conductive paste as a whole. In addition, preferably, the dispersant comprises an acid dispersant. In addition, preferably, the conductive powder comprises at least one metal powder selected from the group consisting of Ni, Pd, Pt, Au, Ag, Cu and their alloys. In addition, preferably, the average particle size of the conductive powder is 0.05 μm or more and 1.0 μm or less. In addition, preferably, the ceramic powder comprises barium titanate. Preferably, the average particle size of the ceramic powder is 0.01 μm or more and 0.5 μm or less. In addition, preferably, the conductive paste comprises a ceramic powder of 1 mass % or more and 20 mass % or less relative to the conductive paste as a whole. In addition, preferably, the binder resin contains a cellulose resin. In addition, preferably, the conductive paste is -1 The viscosity is below 3Pa·S, and the shear rate is 10000sec -1The viscosity is 1 Pa·S or less. Preferably, the average height (Wc) of the waviness curve elements of the dry film obtained by gravure printing the conductive paste at a printing speed of 30 m / min and a film thickness of 0.50 μm to 2 μm is 0.5 μm or less.
[0021] In a second aspect of the present invention, there is provided an electronic component formed using the above-mentioned conductive paste.
[0022] According to a third aspect of the present invention, there is provided a multilayer ceramic capacitor including at least a laminated body in which a dielectric layer and an internal electrode layer are laminated, wherein the internal electrode layer is formed using the above-mentioned conductive paste for gravure printing.
[0023] Effects of the Invention
[0024] The conductive paste of the present invention can reduce the waviness of the surface of the dried film even when the dried film is formed by gravure printing. In addition, the internal electrode layer formed by using the conductive paste of the present invention can manufacture a highly reliable multilayer ceramic capacitor with high productivity even when the internal electrode layer is formed into a thin film electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 and 2 are a perspective view and a cross-sectional view showing a multilayer ceramic capacitor according to an embodiment. DETAILED DESCRIPTION
[0026] [Conductive paste]
[0027] The conductive paste of the present embodiment includes conductive powder, ceramic powder, a dispersant, a binder resin, and an organic solvent. Hereinafter, each component will be described in detail.
[0028] (Conductive powder)
[0029] As the conductive powder, there is no particular limitation, and metal powder can be used, for example, powders of one or more selected from Ni, Pd, Pt, Au, Ag, Cu and their alloys can be used. Among them, from the viewpoints of conductivity, corrosion resistance and cost, powder of Ni or its alloy (hereinafter sometimes referred to as "Ni powder") is preferred. As a Ni alloy, for example, an alloy of Ni and at least one element selected from the group consisting of Mn, Cr, Co, Al, Fe, Cu, Zn, Ag, Au, Pt and Pd can be used. The content of Ni in the Ni alloy is, for example, 50% by mass or more, preferably 80% by mass or more. In addition, in order to suppress the rapid gas generation caused by partial thermal decomposition of the binder resin during the debonding process, the Ni powder can contain element S of about hundreds of ppm.
[0030] The average particle size of the conductive powder is preferably 0.05 μm or more and 1.0 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less. When the average particle size of the conductive powder is within the above range, it can be used as a slurry for internal electrodes of thin-film multilayer ceramic capacitors (multilayer ceramic components), for example, the smoothness of the dry film and the density of the dry film are improved. The average particle size is a value obtained by observation based on a scanning electron microscope (SEM), and is an average value (SEM average particle size) obtained by measuring the particle sizes of multiple particles one by one from an image obtained by observation by SEM at a magnification of 10,000 times.
[0031] The content of the conductive powder is preferably 30% by mass or more and less than 70% by mass, more preferably 40% by mass or more and 60% by mass or less, relative to the entire conductive paste. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent.
[0032] (Ceramic powder)
[0033] The ceramic powder is not particularly limited. For example, in the case of a slurry for internal electrodes of a multilayer ceramic capacitor, a known ceramic powder is appropriately selected according to the type of multilayer ceramic capacitor to be used. As the ceramic powder, for example, a perovskite oxide containing Ba and Ti can be used, preferably containing barium titanate (BaTiO3).
[0034] As the ceramic powder, a ceramic powder containing barium titanate as a main component and oxides as a secondary component can also be used. As oxides, oxides of Mn, Cr, Si, Ca, Ba, Mg, V, W, Ta, Nb and one or more rare earth elements can be listed. In addition, as the ceramic powder, for example, a ceramic powder of a perovskite-type oxide ferroelectric in which the Ba atoms and Ti atoms of barium titanate (BaTiO3) are replaced with other atoms such as Sn, Pb, Zr, etc. can be used.
[0035] When used as a conductive paste for internal electrodes, the ceramic powder can use the same composition as the dielectric ceramic powder constituting the green sheet of the multilayer ceramic capacitor (electronic component). In this way, the generation of cracks caused by the shrinkage mismatch at the interface between the dielectric layer and the internal electrode layer during the sintering process can be suppressed. As such ceramic powder, in addition to the above, for example, oxides such as ZnO, ferrite, PZT, BaO, Al2O3, Bi2O3, R (rare earth element) 2O3, TiO2, and Nd2O3 can also be listed. It should be noted that one ceramic powder can be used, or two or more kinds can be used.
[0036] The average particle size of the ceramic powder is, for example, greater than 0.01 μm and less than 0.5 μm, preferably greater than 0.01 μm and less than 0.3 μm. By making the average particle size of the ceramic powder within the above range, when used as an internal electrode slurry, a sufficiently thin and uniform internal electrode can be formed. The average particle size is a value obtained by observation based on a scanning electron microscope (SEM), and is an average value (SEM average particle size) obtained by measuring the particle sizes of multiple particles one by one from an image obtained by observation by SEM at a magnification of 50,000 times.
[0037] The content of the ceramic powder is preferably 1% to 20% by mass, more preferably 3% to 15% by mass, relative to the entire conductive paste. When the content of the ceramic powder is within the above range, dispersibility and sinterability are excellent.
[0038] The content of the ceramic powder is preferably 1 part by mass or more and 30 parts by mass or less, and more preferably 3 parts by mass or more and 30 parts by mass or less, based on 100 parts by mass of the conductive powder.
[0039] (Binder resin)
[0040] The binder resin is not particularly limited, and known resins can be used. Examples of the binder resin include cellulose resins such as methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and nitrocellulose, acrylic resins, and butyral resins such as polyvinyl butyral. Among them, from the viewpoints of solubility in solvents and combustion decomposition properties, it is preferred to include a cellulose resin, and more preferably to include ethyl cellulose.
[0041] In addition, when used as an internal electrode paste, from the viewpoint of improving the bonding strength with the green sheet, a butyral resin may be included, or a butyral resin may be used alone. When the binder resin includes a butyral resin, the viscosity can be easily adjusted to be suitable for gravure printing, and the bonding strength with the green sheet can be further improved. In the binder resin, for example, 20% or more of the butyral resin may be included relative to the entire binder resin, or 30% or more of the butyral resin may be included.
[0042] When the binder resin includes a cellulose resin and a butyral resin, the binder resin may include 20% to 80% by mass of acetal resin, 30% to 80% by mass, or 30% to 60% by mass, relative to the total content (100% by mass) of the cellulose resin and the butyral resin.
[0043] In addition, the degree of polymerization and the weight average molecular weight of the binder resin can be appropriately adjusted within the above range according to the required viscosity of the conductive paste.
[0044] For example, when a cellulose resin is included as a binder resin, the weight average molecular weight (Mw) may be 10,000 to 300,000, 30,000 to 200,000, or 50,000 to 150,000. When the Mw of the cellulose resin is within the above range, the viscosity of the conductive paste can be adjusted to an appropriate range, and the waviness of the surface of the dried film can be reduced.
[0045] In addition, the hydroxyl value of the cellulose resin is not particularly limited, preferably 0.1 mgKOH / g or more and 15 mgKOH / g or less, more preferably 0.5 mgKOH / g or more and 7 mgKOH / g or less, and further preferably 1.5 mgKOH / g or more and 3 mgKOH / g or less. When the hydroxyl value of the cellulose resin is within the above range, the conductive powder and ceramic powder have excellent dispersibility, so they can be suitable for conductive paste for gravure printing. It should be noted that the hydroxyl value is a value measured according to JIS K 0070, which is a value indicating the number of mg of potassium hydroxide equivalent to the hydroxyl group in 1 g of the sample.
[0046] The ethoxy content of the cellulose resin is not particularly limited, and may be, for example, 40% by mass or more and 55% by mass or less, 45% by mass or more and 52% by mass or less, or 48% by mass or more and 50% by mass or less.
[0047] For example, when a butyral resin is included as a binder resin, the weight average molecular weight (Mw) may be 30,000 to 300,000, 50,000 to 200,000, or 100,000 to 150,000. When the Mw of the butyral resin is within the above range, the viscosity of the conductive paste can be adjusted to a suitable range, and the waviness of the surface of the dried film can be reduced.
[0048] The content of the binder resin is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 7% by mass, relative to the entire conductive paste. When the content of the binder resin is within the above range, conductivity and dispersibility are excellent.
[0049] The content of the binder resin is preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 1 part by mass or more and 14 parts by mass or less, based on 100 parts by mass of the conductive powder.
[0050] (Organic Solvent)
[0051] The conductive paste involved in this embodiment includes at least one selected from the group consisting of isobornyl acetate (IBA), methyl isobutyl ketone (MIBK) and diisobutyl ketone (DIBK) (hereinafter referred to as the "first organic solvent") as an organic solvent, preferably including one or both of isobornyl acetate and diisobutyl ketone, and more preferably including isobornyl acetate. By including the above-mentioned organic solvent (hereinafter also referred to as the "first organic solvent"), the conductive paste can reduce the waviness of the film surface when forming a dry film. It should be noted that the first organic solvent can be used alone or in combination of two or more. In addition, when two or more organic solvents are included as the first organic solvent, isobornyl acetate and diisobutyl ketone can be included.
[0052] The content of the first organic solvent relative to the total amount of the conductive paste may be 3% to 60% by mass, 5% to 40% by mass, 10% to 30% by mass, or 10% to 20% by mass. In addition, even if the content of the first organic solvent is 5% to 10% by mass, the waviness of the dried film surface can be reduced.
[0053] In addition, when the first organic solvent contains isobornyl acetate (IBA), the content of isobornyl acetate is preferably 4% by mass or more, more preferably 5% by mass or more, and further preferably 8% by mass or more relative to the total amount of the conductive paste. When the content of isobornyl acetate is within the above range, the waviness of the film surface when forming a dry film can be further reduced. In addition, the content of isobornyl acetate can be 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less relative to the total amount of the conductive paste.
[0054] In addition, when the first organic solvent includes diisobutyl ketone (DIBK), the content of diisobutyl ketone is preferably 4% by mass or more, and more preferably 5% by mass or more relative to the total amount of the conductive paste. When the content of diisobutyl ketone is within the above range, the waviness of the film surface when forming a dry film can be further reduced, and further, it can be easily adjusted to a viscosity suitable for gravure printing. Further, when diisobutyl ketone (DIBK) is included, the drying property is excellent, and the process (film-making process) of applying the conductive paste on the raw sheet and drying it by gravure printing can be short. In addition, relative to the total amount of the conductive paste, the content of diisobutyl ketone can be 30% by mass or less, 20% by mass or less, 10% by mass or less, or 7% by mass or less.
[0055] It should be noted that, as an organic solvent, an organic solvent other than the first organic solvent may be contained. As an organic solvent other than the first organic solvent (other organic solvent), there is no particular limitation, and a known organic solvent capable of dissolving the above-mentioned binder resin may be used. As other organic solvents, for example, glycol ether solvents, acetate solvents, ketone solvents, terpene solvents, petroleum hydrocarbon solvents including aliphatic hydrocarbon solvents, etc. may be cited. It should be noted that, as other organic solvents, one kind may be used, or two or more kinds may be used.
[0056] Examples of the glycol ether solvent include (di)glycol ethers such as diethylene glycol mono-2-ethylhexyl ether, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol monohexyl ether, ethylene glycol monohexyl ether, and diethylene glycol monomethyl ether; and propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether (PNB).
[0057] Examples of the acetate solvent include glycol ether acetates such as isobornyl propionate, isobornyl butyrate, isobornyl isobutyrate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, dipropylene glycol methyl ether acetate, 3-methoxy-3-methylbutyl acetate, and 1-methoxypropyl-2-acetate, ethyl acetate, propyl acetate, isobutyl acetate, and butyl acetate.
[0058] Examples of the ketone solvent include methyl ethyl ketone and the like.
[0059] Examples of the terpene solvent include terpineol, dihydroterpineol (DHT), and dihydroterpineol acetate.
[0060] Examples of petroleum hydrocarbon solvents including aliphatic hydrocarbon solvents include solvents including tridecane, nonane, cyclohexane, etc., mineral spirits (MA), cycloparaffinic solvents, etc. Among them, it is preferred to include mineral spirits, and it may also include mineral spirits as a main component (the solvent with the highest content among petroleum hydrocarbon solvents). It should be noted that mineral spirits may include chain saturated hydrocarbons as a main component, and may also contain 20% by mass or more of chain saturated hydrocarbons relative to the entire mineral spirits.
[0061] As other organic solvents, for example, terpene solvents and aliphatic hydrocarbon solvents may be included, or only terpene solvents or only aliphatic hydrocarbon solvents may be included. In addition, as other organic solvents, for example, when a terpene solvent is included, the content of the terpene solvent may be 5% by mass or more and 40% by mass or less, or 10% by mass or more and 25% by mass or less, relative to the total amount of the conductive paste. In addition, as other organic solvents, for example, when an aliphatic hydrocarbon solvent is included, the content of the aliphatic hydrocarbon solvent may be 5% by mass or more and 25% by mass or less, or 5% by mass or more and 15% by mass or less, relative to the total amount of the conductive paste.
[0062] The content of the organic solvent (total) is preferably 20% by mass or more and 60% by mass or less, and more preferably 25% by mass or more and 45% by mass or less relative to the total amount of the conductive paste. When the content of the organic solvent is within the above range, the conductivity and dispersibility are excellent.
[0063] The content of the organic solvent is preferably 50 parts by mass or more and 130 parts by mass or less, and more preferably 60 parts by mass or more and 90 parts by mass or less, based on 100 parts by mass of the conductive powder. When the content of the organic solvent is within the above range, the conductivity and dispersibility are excellent.
[0064] (Dispersant)
[0065] As the dispersant, a known dispersant can be used. As the dispersant, for example, an acidic dispersant can be included. In addition, as the acidic dispersant, a dispersant having a carboxyl group other than the dicarboxylic acid described later can also be included. It should be noted that in this specification, as described later, the dicarboxylic acid and the dispersant are separately specified in view of the effect of the dicarboxylic acid on suppressing the separation of the conductive powder and the ceramic powder.
[0066] For example, when comb carboxylic acid is used as a dispersant, the dispersibility of the conductive paste is improved by containing the comb carboxylic acid. It should be noted that the dispersant may be used alone or in combination of two or more. The conductive paste according to the present embodiment contains a dispersant to improve its dispersibility.
[0067] As the dispersant, for example, an acidic dispersant having a hydrocarbon group may be included. As such an acidic dispersant, for example, acidic dispersants such as higher fatty acids and polymer surfactants, phosphoric acid dispersants, etc. may be cited. These dispersants may be used alone or in combination of two or more.
[0068] The higher fatty acid may be an unsaturated carboxylic acid or a saturated carboxylic acid, and is not particularly limited, and examples thereof include higher fatty acids having 11 or more carbon atoms, such as stearic acid, oleic acid, myristic acid, palmitic acid, linoleic acid, lauric acid, and linolenic acid. Among them, oleic acid or stearic acid is preferred.
[0069] The other acidic dispersants are not particularly limited, and examples thereof include alkyl monoamine salt-type dispersants represented by monoalkylamine salts.
[0070] As the alkyl monoamine type, for example, oleoylsarcosine which is a compound of glycine and oleic acid, and an amide compound using a higher fatty acid such as stearic acid or lauric acid instead of oleic acid are preferred.
[0071] In addition, the dispersant may also include dispersants other than acidic dispersants. Examples of dispersants other than acidic dispersants include alkaline dispersants, nonionic dispersants, amphoteric dispersants, etc. These dispersants may be used alone or in combination of two or more.
[0072] Examples of the alkaline dispersant include aliphatic amines such as laurylamine, abietamine, cetylamine, myristicamine, and stearylamine. When the conductive paste contains the acidic dispersant and the alkaline dispersant, the dispersibility is better and the viscosity stability over time is also excellent.
[0073] Relative to the conductive paste as a whole, it is preferred to contain a dispersant of 3% by mass or less. The upper limit of the content of the dispersant is preferably 2% by mass or less, more preferably 1% by mass or less. The lower limit of the content of the dispersant is not particularly limited, for example, 0.01% by mass or more, preferably 0.05% by mass or more. When the content of the dispersant is within the above range, the dispersibility of the conductive paste can be improved, and the paste viscosity can be adjusted to an appropriate range. In addition, the deterioration of the drying property after printing can be prevented, and the sheet erosion and the poor peeling of the raw sheet can be further suppressed.
[0074] In addition, based on 100 parts by mass of the conductive powder, it is preferred to contain a dispersant of 0.01 parts by mass or more and 5 parts by mass or less, more preferably 0.05 parts by mass or more and 3 parts by mass or less, and further preferably 0.4 parts by mass or more and 3 parts by mass or less. When the content of the dispersant is within the above range, the dispersibility of the conductive powder and ceramic powder, and the smoothness of the surface of the dried electrode after coating are more excellent, and the viscosity of the conductive paste can be adjusted to an appropriate range. In addition, the deterioration of the drying property after printing can be prevented, and the sheet erosion and the poor peeling of the raw sheet can be further suppressed. In addition, the dispersant may also include an acidic dispersant and an alkaline dispersant. In the case of including an acidic dispersant and an alkaline dispersant as the dispersant, it is preferred that the content of the acidic dispersant is more than the content of the alkaline dispersant. For example, the content of the alkaline dispersant can be 0.1 times or more and less than 1 times, 0.3 times or more and 0.8 times or less relative to the content of the acidic dispersant.
[0075] (Dicarboxylic Acid)
[0076] The conductive paste of the present embodiment may contain dicarboxylic acid as an additive. In the conductive paste for gravure printing, by containing a specific amount of dicarboxylic acid, the separation of the conductive powder and the ceramic powder can be suppressed, and the generation of floating white of a white separation layer containing ceramic powder on the upper part when the conductive paste is prepared can be suppressed. In addition, when the conductive paste of the present embodiment is used to form an internal electrode layer, a higher coverage can be achieved.
[0077] Dicarboxylic acid is a carboxylic acid-based additive having two carboxyl groups (COO-groups). Examples of dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalene dicarboxylic acid; aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedicarboxylic acid, and azelaic acid; dibasic acids such as dimer acid produced by dimerization of unsaturated fatty acids having 12 to 28 carbon atoms; alicyclic dicarboxylic acids such as hydrogenated dimer acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 4-methylhexahydrophthalic anhydride, 3-methylhexahydrophthalic anhydride, 2-methylhexahydrophthalic anhydride, dicarboxy hydrogenated bisphenol A, dicarboxy hydrogenated bisphenol S, hydrogenated naphthalene dicarboxylic acid, and tricyclodecane dicarboxylic acid; and derivatives thereof, of which derivatives of succinic acid are preferred.
[0078] In addition, the average molecular weight of the dicarboxylic acid is not particularly limited, and for example, it may be less than 1000, less than 500, or less than 400. When the average molecular weight of the dicarboxylic acid is within the above range, a higher separation inhibition effect can be obtained. The average molecular weight of the dicarboxylic acid may be, for example, more than 100, or more than 200.
[0079] In addition, in the conductive paste involved in the present embodiment, relative to the conductive paste as a whole, a dicarboxylic acid of 0.05 mass % or more and less than 3.0 mass % may be included, preferably 0.1 mass % or more and 1.0 mass % or less. In addition, the range of the upper limit of the content of the dicarboxylic acid may be 0.5 mass % or less. In the case where the content of the dicarboxylic acid is 3.0 mass % or more, in the printing and drying process, the drying becomes insufficient, the internal electrode layer becomes soft, and sometimes a stacking offset is generated in the subsequent stacking process, or the residual dicarboxylic acid is gasified during firing, and internal stress is generated due to the gasified gas component, or the structural damage of the laminate is generated.
[0080] It should be noted that, when the conductive paste contains a dispersant (except dicarboxylic acid) and a dicarboxylic acid, the total content of the dispersant and the dicarboxylic acid can be greater than 0.05 mass % and less than 3.0 mass %, or greater than 0.1 mass % and less than 2.0 mass %, or greater than 0.1 mass % and less than 1.0 mass %, relative to the entire conductive paste.
[0081] It should be noted that the conductive paste according to the present embodiment may not contain dicarboxylic acid. Even when the conductive paste according to the present embodiment does not contain dicarboxylic acid, as described above, the waviness of the dried film surface can be reduced by containing a specific organic solvent.
[0082] (Other additives)
[0083] The conductive paste of the present embodiment may contain other additives in addition to the above-mentioned components as necessary. As other additives, for example, conventionally known additives such as a defoamer, a plasticizer, a surfactant, and a thickener may be used.
[0084] (Conductive paste)
[0085] The method for manufacturing the conductive paste involved in the present embodiment is not particularly limited, and a conventionally known method can be used. For example, the conductive paste can be manufactured by stirring and kneading the above-mentioned components through a three-roll mill, a ball mill, a mixer, etc. It should be noted that, for dicarboxylic acid (separation inhibitor), it is preferably weighed and added when stirring and kneading by a mixer, etc., like other materials, but even if it is added as a separation inhibitor to the material after stirring and kneading (dispersion), the same separation inhibition effect can be obtained.
[0086] Conductive paste at a shear rate of 100 sec -1 The viscosity is preferably 3 Pa·S or less. -1When the viscosity is within the above range, it can be used as a conductive paste for gravure printing. If it exceeds the above range, the viscosity is sometimes too high and not suitable for gravure printing. -1 The lower limit of the viscosity at the time of 0.5 % is not particularly limited, but is, for example, 0.2 Pa·S or more.
[0087] In addition, the conductive paste is subjected to a shear rate of 10000 sec -1 The viscosity is preferably 1 Pa·S or less. At a shear rate of 10000 sec -1 When the viscosity is within the above range, it can be used as a conductive paste for gravure printing. When it exceeds the above range, the viscosity is sometimes too high and not suitable for gravure printing. -1 The lower limit of the viscosity at the time of 0.05 Pa·S is not particularly limited, but is, for example, 0.05 Pa·S or more.
[0088] The conductive paste can be suitably used in electronic components such as multilayer ceramic capacitors. The multilayer ceramic capacitor has a dielectric layer formed using a dielectric green sheet and an internal electrode layer formed using a conductive paste.
[0089] As a dry film obtained by gravure printing a conductive paste under the conditions of a printing speed of 30 m / min and a film thickness of 0.50 μm to 2 μm, the average height (Wc) of the waviness curve element when the cutoff value (λc = 0.08 mm) is applied is preferably less than 0.5 μm, more preferably less than 0.47 μm, more preferably less than 0.45 μm, more preferably less than 0.4 μm, and further preferably less than 0.35 μm.
[0090] It should be noted that the average height (Wc) of the corrugation curve element can be measured in accordance with JIS B 0601:2013. The average height (Wc) of the corrugation curve element represents the average value of the height (Zti) of the corrugation curve element (contour curve element) under the reference length. The contour curve element is an element that sets adjacent peaks and valleys as a group, and the height of the contour curve element is equivalent to the height difference between adjacent peaks and valleys. It should be noted that the peaks (valleys) constituting the contour element have regulations on the minimum height and minimum length, and the height (depth) of less than 10% of the maximum height or the length of less than 1% of the length of the calculation interval is regarded as noise as part of the continuous valleys (peaks) before and after.
[0091] [Electronic components]
[0092] Hereinafter, embodiments of the electronic component and the like of the present invention will be described with reference to the accompanying drawings. In the accompanying drawings, the electronic component and the like may be shown schematically or with a changed scale as appropriate. Figure 1 The position and direction of the member are described using an XYZ orthogonal coordinate system shown in FIG. In the XYZ orthogonal coordinate system, the X direction and the Y direction are horizontal directions, and the Z direction is a vertical direction (up and down direction).
[0093] Figure 1 A in and Figure 1 B in FIG. 1 is a diagram showing a multilayer ceramic capacitor 1 as an example of the electronic component according to the embodiment. The multilayer ceramic capacitor 1 includes a ceramic multilayer body 10 in which dielectric layers 12 and internal electrode layers 11 are alternately stacked, and external electrodes 20 .
[0094] The following is a method for manufacturing a multilayer ceramic capacitor using the above-mentioned conductive paste. First, a conductive paste is printed on a ceramic green sheet and dried to form a dry film, and a plurality of ceramic green sheets having the dry film on the upper surface are stacked by pressure bonding to obtain a laminated body, and then the laminated body is fired to be integrated, thereby manufacturing a ceramic laminated body 10 in which internal electrode layers 11 and dielectric layers 12 are alternately stacked. Thereafter, a pair of external electrodes are formed at both ends of the ceramic laminated body 10 to manufacture a multilayer ceramic capacitor 1. The following is a more detailed description.
[0095] First, a ceramic green sheet as an unfired ceramic sheet is prepared. As the ceramic green sheet, for example, a dielectric layer slurry obtained by adding an organic binder such as polyvinyl butyral and a solvent such as terpineol to a raw material powder of a predetermined ceramic such as barium titanate is coated on a supporting film such as a PET film in a sheet shape and dried to remove the solvent. It should be noted that the thickness of the dielectric layer composed of the ceramic green sheet is not particularly limited, but from the perspective of the miniaturization requirement of the multilayer ceramic capacitor, it is preferably 0.05 μm or more and 3 μm or less.
[0096] Next, a plurality of sheets are prepared in which a dry film is formed on one surface of the ceramic green sheet by printing and applying the above-mentioned conductive paste on one surface of the ceramic green sheet using a gravure printing method and drying the sheet. It should be noted that from the viewpoint of the requirement for thinning the internal electrode layer 11, the thickness of the dry film formed by the conductive paste is preferably 1 μm or less after drying.
[0097] Next, the ceramic green sheets are peeled off from the support film, and the ceramic green sheets and the dry films formed on one surface of the ceramic green sheets are alternately stacked, and then heated and pressurized to obtain a laminate. It should be noted that a protective ceramic green sheet not coated with the conductive paste may be further arranged on both surfaces of the laminate.
[0098] Next, after the laminate is cut into a predetermined size to form a raw chip, the raw chip is subjected to a debinding treatment and fired in a reducing atmosphere, thereby manufacturing a laminated ceramic fired body (ceramic laminate 10). It should be noted that the atmosphere in the debinding treatment is preferably air or N2 gas atmosphere. The temperature during the debinding treatment is, for example, above 200°C and below 400°C. In addition, the holding time of the above temperature during the debinding treatment is preferably above 0.5 hours and below 24 hours. In addition, in order to suppress the oxidation of the metal used in the internal electrode layer, the firing is performed in a reducing atmosphere. In addition, the temperature during the firing of the laminate is, for example, above 1000°C and below 1350°C, and the holding time of the temperature during the firing is, for example, above 0.5 hours and below 8 hours.
[0099] By firing the green chip, the organic binder in the ceramic green sheet is completely removed, and the raw material powder of the ceramic is fired to form a ceramic dielectric layer 12. In addition, the organic vehicle in the dry film is removed, and the nickel powder or the alloy powder with nickel as the main component is sintered or melted to form an internal electrode layer 11, and then a multilayer ceramic fired body is formed in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. It should be noted that from the viewpoint of bringing oxygen into the interior of the dielectric layer to improve reliability and suppressing reoxidation of the internal electrode, the fired multilayer ceramic fired body can be annealed.
[0100] Then, a pair of external electrodes 20 are provided on the manufactured multilayer ceramic fired body to manufacture the multilayer ceramic capacitor 1. For example, the external electrode 20 includes an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. It should be noted that as a material of the external electrode 20, for example, copper, nickel, or an alloy thereof can be preferably used. It should be noted that the electronic component can also use electronic components other than the multilayer ceramic capacitor.
[0101] Example
[0102] Hereinafter, the present invention will be described in detail based on Examples and Comparative Examples, but the present invention is not limited to the Examples at all.
[0103] [Evaluation method]
[0104] (Viscosity of conductive paste)
[0105] The viscosity of the conductive paste after production was measured using a rheometer (manufactured by Anton Paar Japan Co., Ltd.: Rheometer MCR302). The viscosity was measured using a cone plate with a cone angle of 1° and a diameter of 25 mm at a shear rate (shear speed) of 100 sec. -1 and 10000sec-1 The value is measured under the conditions of .
[0106] (Evaluation of dried film)
[0107] The conductive paste was printed on a small gravure printing machine (manufactured by Kurabo Co., Ltd., GP-10TYPEII) at a printing speed of 30 m / min and a conductive powder (Ni powder) of 0.7 mg / cm 2 After printing on a dielectric sheet in an amount of , it was dried in a box dryer at 80°C for 4 minutes and taken out to obtain a dry film (2.5 mm wide x 5 mm long) for evaluation. The film thickness of the dry film was 0.50 μm or more and 2 μm or less.
[0108] The waviness of the dry film surface was evaluated using a laser microscope (VK-100 manufactured by KEYENCE, measuring objective lens ×20, measuring length: 2000 μm) with the average height (Wc) of the waviness curve element when a cutoff value (λc = 0.08 mm) was applied. It should be noted that the average height (Wc) of the waviness curve element was the average value of multiple evaluations.
[0109] [Materials used]
[0110] (Conductive powder)
[0111] As the conductive powder, Ni powder (SEM average particle size: 0.2 μm) was used.
[0112] (Ceramic powder)
[0113] As the ceramic powder, barium titanate (BaTiO 3 ; SEM average particle size: 0.10 μm) was used.
[0114] (Binder resin)
[0115] As the binder resin, polyvinyl butyral resin or ethyl cellulose was used.
[0116] (additive)
[0117] As the additive, dicarboxylic acid is used.
[0118] (Dispersant)
[0119] As the dispersant, an acidic dispersant and an alkaline dispersant were used. In addition, as the acidic dispersant, a comb carboxylic acid and a phosphoric acid dispersant were used, and as the alkaline dispersant, oleylamine was used.
[0120] (Organic Solvent)
[0121] As organic solvents, isobornyl acetate (IBA), methyl isobutyl ketone (MIBK), diisobutyl ketone (DIBK), dihydroterpineol (DHT), propylene glycol monobutyl ether (PNB), diethylene glycol monobutyl ether acetate (BCA), propylene glycol monomethyl ether acetate (PMA), diethylene glycol monomethyl ether (DEGME), and mineral spirits (MA) were used.
[0122] [Example 1]
[0123] Conductive powder 50 mass%, ceramic powder 12.5 mass%, dispersant 0.5 mass% (acidic dispersant 0.3 mass%, alkaline dispersant 0.2 mass%), dicarboxylic acid 0.2 mass%, binder resin 2.5 mass% (polyvinyl butyral resin: ethyl cellulose = 1:2 (mass ratio)), and IBA 4.1 mass%, MA 12.0 mass% and DHT as the balance as an organic solvent were added and mixed in such a way that the total amount was 100 mass%, and these materials were prepared to prepare a conductive paste. The content of additives and the average height of the waviness of the conductive paste is shown in Table 1.
[0124] [Examples 2 to 18]
[0125] In Examples 2 to 18, conductive pastes were prepared and evaluated in the same manner as in Example 1 except that the presence or absence of additives, the type and content of the organic solvent were changed as shown in Table 1. Table 1 shows the contents of additives and the like in the conductive paste and the evaluation results Wc of the average height of the waviness.
[0126] [Comparative Examples 1 to 4]
[0127] Conductive pastes were prepared and evaluated in the same manner as in Example 1 except that the organic solvents used were 13.7 mass % of MA and the balance of PNB (Comparative Example 1), 13.7 mass % of MA and the balance of DHT (Comparative Example 2), 12 mass % of MA, 5.9 mass % of PMA and the balance of DHT (Comparative Example 3), and 12 mass % of MA, 5.9 mass % of DEGME and the balance of DHT (Comparative Example 4). The contents of additives and the like in the conductive pastes and the evaluation results Wc of the average height of the waviness are shown in Table 1.
[0128]
[0129] (Evaluation results)
[0130] The conductive pastes of Examples 1 to 18 had smaller average heights (Wc) of waviness curve elements in the dried films than the conductive pastes of Comparative Examples 1 to 4 in which the first organic solvent (IBA, MIBK, DIBK) was not used.
[0131] In addition, in all the conductive pastes of the examples and comparative examples shown in Table 1, the shear rate was 100 sec. -1 The viscosity is below 3Pa·S and the shear rate is 10000sec -1 The viscosity at 1 Pa·S or less was confirmed to be suitable for gravure printing.
[0132] Industrial Applicability
[0133] When the conductive paste of the present invention is used to form the internal electrodes of a multilayer ceramic capacitor, a multilayer ceramic capacitor with high reliability can be obtained with high productivity. Therefore, the conductive paste of the present invention can be particularly suitably used as a raw material for the internal electrodes of multilayer ceramic capacitors that are chip components of increasingly miniaturized electronic devices such as mobile phones and digital devices, and can be suitably used as a conductive paste for gravure printing.
[0134] It should be noted that the technical scope of the present invention is not limited to the methods described in the above-mentioned embodiments, etc. Sometimes one or more elements described in the above-mentioned embodiments, etc. are omitted. In addition, the elements described in the above-mentioned embodiments, etc. can be appropriately combined. In addition, as long as it is within the scope permitted by law, the disclosure of all the documents cited in the above-mentioned embodiments, etc. is cited as part of the record of this article.
[0135] Sometimes one or more elements described in the above embodiments are omitted. In addition, the elements described in the above embodiments may be appropriately combined. In addition, as long as it is within the scope permitted by law, the contents of all documents cited in Japanese Patent Application No. 2020-179986, Japanese Patent Application No. 2021-093300, and this specification are cited as part of the description of this article.
[0136] Description of Reference Numerals
[0137] 1: Multilayer ceramic capacitor;
[0138] 10: Ceramic laminate;
[0139] 11: internal electrode layer;
[0140] 12: dielectric layer;
[0141] 20: external electrode;
[0142] 21: external electrode layer;
[0143] 22: Electroplating layer.
Claims
1. A conductive paste for gravure printing, comprising conductive powder, ceramic powder, a dispersant, a binder resin and an organic solvent, characterized in that: The organic solvent is composed of the first organic solvent and an organic solvent other than the first organic solvent. The first organic solvent is at least one selected from the group consisting of isobornyl acetate, methyl isobutyl ketone and diisobutyl ketone, The organic solvent other than the first organic solvent comprises a terpene solvent and / or an aliphatic hydrocarbon solvent, The content of the first organic solvent is 3% by mass or more and 60% by mass or less relative to the total amount of the conductive paste. When the cutoff value λc=0.08 mm is applied to a dry film obtained by gravure printing the conductive paste at a printing speed of 30 m / min and a film thickness of 0.50 μm to 2 μm, the average height Wc of the waviness curve elements is 0.50 μm or less.
2. The conductive paste for gravure printing according to claim 1, characterized in that: The conductive paste for gravure printing further contains 0.05 mass % or more and less than 3.0 mass % of a dicarboxylic acid based on the entire conductive paste.
3. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The conductive paste for gravure printing contains the organic solvent in an amount of 10% by mass or more and 60% by mass or less relative to the entire conductive paste. When the terpene solvent is contained, the content of the terpene solvent is 10 mass % or more and 25 mass % or less, When the aliphatic hydrocarbon solvent is contained, the content of the aliphatic hydrocarbon solvent is 5 mass % or more and 25 mass % or less.
4. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The conductive paste for gravure printing contains the dispersant in an amount of 0.01% by mass or more and 3.0% by mass or less based on the entire conductive paste.
5. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The dispersant includes an acid-based dispersant.
6. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The conductive powder includes at least one metal powder selected from the group consisting of Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof.
7. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The conductive powder has an average particle size of 0.05 μm or more and 1.0 μm or less.
8. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The ceramic powder includes barium titanate.
9. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The ceramic powder has an average particle size of 0.01 μm or more and 0.5 μm or less.
10. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The conductive paste for gravure printing contains the ceramic powder in an amount of 1% by mass or more and 20% by mass or less based on the entire conductive paste.
11. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The binder resin includes a cellulose-based resin.
12. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The conductive paste for gravure printing is subjected to a shear rate of 100 sec -1 The viscosity is below 3Pa·S, and the shear rate is 10000sec -1 The viscosity is 1 Pa·S or less.
13. The conductive paste for gravure printing according to claim 1 or 2, characterized in that: The average height of waviness curve elements of a dry film obtained by gravure printing the conductive paste for gravure printing at a printing speed of 30 m / min and a film thickness of 0.50 μm to 2 μm is 0.47 μm or less.
14. An electronic component, characterized in that: The electronic component is an electronic component formed using the conductive paste for gravure printing according to any one of claims 1 to 13.
15. A multilayer ceramic capacitor, characterized in that: The multilayer ceramic capacitor includes at least a laminated body formed by laminating a dielectric layer and an internal electrode layer. The internal electrode layer is formed using the conductive paste for gravure printing according to any one of claims 1 to 13.
